1998
DOI: 10.1039/a707643f
|View full text |Cite
|
Sign up to set email alerts
|

New supramolecular arrays based on interactions between carboxylate and urea groups: solid-state and solution behavior

Abstract: The ureaÈcarboxylate interaction is introduced as a potentially general motif for the control of solid-state packing patterns. We show that simple phenylurea carboxylate derivatives can form extended hydrogen-bonded ribbons in the crystal in which the zig-zag shape of the aggregate is controlled by the relative orientation of the two substituents about the phenyl core. We also show that an alternative type of aggregation may occur in solution involving the formation of cyclic aggregates. Again, the size and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…[1,2] It is known to form inclusion complexes with n-alkanes (! 7 carbon atoms) [3][4][5][6] and some functionalized longchain molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] It is known to form inclusion complexes with n-alkanes (! 7 carbon atoms) [3][4][5][6] and some functionalized longchain molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such molecules lie at the forefront of modern chemical research [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…One of the few examples of five‐membered supramolecular macrocycles was reported in 1998 by Hamilton and co‐workers . They previously showed that acylaminopyridine and carboxylic acid derivatives could form extended or cyclic aggregates depending on the conditions and the nature of the interacting components.…”
Section: Hydrogen‐bonded Macrocycles In Solutionmentioning
confidence: 99%